2007
DOI: 10.1210/en.2006-1626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Androgens and Estradiol on Spine Synapse Formation in the Prefrontal Cortex of Normal and Testicular Feminization Mutant Male Rats

Abstract: Recent studies suggest that, in female monkeys and rats, estrogens elicit dendritic spine synapse formation in the prefrontal cortex, an area that, similar to the hippocampus, plays a critical role in cognition. However, whether gonadal hormones induce synaptic remodeling in the male prefrontal cortex remains unknown. Here we report that gonadectomy reduced, whereas administration of 5␣-dihydrotestosterone or estradiol-benzoate to castrated male rats increased, the number of medial prefrontal cortical (mPFC) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 28 publications
5
51
0
Order By: Relevance
“…The postsynaptic marker PSD95 is a PDZ-domain protein associated with the PSD and is involved in the anchoring of numerous synaptic components, including NMDA and AMPA receptors and K ϩ channels (37). Gonadal steroids regulate dendritic spine density throughout development and in adulthood (12), with androgen-induced remodeling of neural circuits observed in the medial prefrontal cortex (38), hippocampus (39 -41), and the spinal nucleus of the bulbocavernosus (42). The present results indicate that the SCN is a novel locus of hormone-mediated structural plasticity in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The postsynaptic marker PSD95 is a PDZ-domain protein associated with the PSD and is involved in the anchoring of numerous synaptic components, including NMDA and AMPA receptors and K ϩ channels (37). Gonadal steroids regulate dendritic spine density throughout development and in adulthood (12), with androgen-induced remodeling of neural circuits observed in the medial prefrontal cortex (38), hippocampus (39 -41), and the spinal nucleus of the bulbocavernosus (42). The present results indicate that the SCN is a novel locus of hormone-mediated structural plasticity in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, testosterone or nonaromatizable DHT ameliorated the reduced CA1 spine density in males (370). As in females, gonadectomy reduced medial prefrontal cortical spines in males, but estradiol benzoate had a more modest effect than DHT in ameliorating this reduction in the mPFC (235). The effects of androgens on hippocampal physiology and cognition in males are discussed in detail later.…”
Section: Estradiol and Progestin Effects In Malesmentioning
confidence: 95%
“…Hajszan et al (235) reported that castrated wild type males displayed a decrease in the number of spine in the mPFC. However, systemic injections of 200 μL of DHT over 2 days reversed this decrease with the density of spines increasing by 136% and restoring the number to sham levels.…”
Section: Androgen-mediated Structural Plasticity In the Prefrontal Comentioning
confidence: 99%
“…Also as in the hippocampus, NMDA receptors play a significant role in this phenomenon, as evidenced by the ability of NMDA receptor antagonists to disrupt PFC-dependent cognition and reduce the number of asymmetric spine synapses (indicative of excitatory input) in the male PFC (Hajszan et al, 2008). However, unlike the hippocampus, estradiol can increase spine synapses in the castrated male rat PFC, albeit not as 186 potently as androgens (Hajszan et al, 2007). Estradiol also maintains dendritic spines in specific cortical regions of female nonhuman primates (Tang et al, 2004) and rats (Wallace et al, 2006), in parallel with positive effects on working memory; preliminary studies indicate that androgens may also positively affect spine synapses in the female PFC (Hajszan et al, 2008).…”
Section: B Preclinical Studiesmentioning
confidence: 99%